Principles of Islamic Education Curriculum Development in Madrasah - Muhammad Dinul Adha; Zulkifli Musthan (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
Background: The development of globalisation and technological revolution has brought significant changes to the field of education, including the development of Islamic Education curriculum in madrasahs. Curriculum must adapt to advances in science and students' needs without neglecting Islamic values as the foundation of education. Objective: This study aims to analyse the principles of Islamic Education curriculum development in madrasahs and their relevance to the challenges of modern education. Method: The study employed a descriptive qualitative approach using a library research method. Data were collected from books, scientific journals, curriculum documents, previous studies, and relevant Islamic sources, then analysed using content analysis techniques. Result: The findings indicate that the development of Islamic Education curriculum in madrasahs is based on the principles of relevance, flexibility, continuity, effectiveness, efficiency, and the integration of Islamic values. These principles play an important role in shaping students who are intellectually, spiritually, and socially competent. Conclusion: The study concludes that Islamic Education curriculum should be developed adaptively and integratively to address the challenges of 21st-century education. Contribution: This study contributes to strengthening the discourse on Islamic Education curriculum development grounded in Islamic values and contemporary educational needs.